2004
DOI: 10.1242/dev.01397
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish and fly Nkx6 proteins have similar CNS expression patterns and regulate motoneuron formation

Abstract: Genes belonging to the Nkx, Gsh and Msx families are expressed in similar dorsovental spatial domains of the insect and vertebrate central nervous system (CNS), suggesting the bilaterian ancestor used this genetic program during CNS development. We have investigated the significance of these similar expression patterns by testing whether Nkx6 proteins expressed in ventral CNS of zebrafish and flies have similar functions. In zebrafish, Nkx6.1 is expressed in early-born primary and later-born secondary motoneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 66 publications
10
96
0
Order By: Relevance
“…Consistent with previous studies, expression of nkx6.1 (Fig. 3C,CЈ ;Cheesman et al, 2004) and nkx6.2 ( Fig. 3E,EЈ; Guner and Karlstrom, 2007) were abolished in embryos treated with cyclopamine at 50% epiboly, whereas dimethyl sulfoxide (DMSO) -treated embryos displayed normal expression of these markers.…”
Section: Characterization Of Dbx Gene Expression In Zebrafish Spinal supporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, expression of nkx6.1 (Fig. 3C,CЈ ;Cheesman et al, 2004) and nkx6.2 ( Fig. 3E,EЈ; Guner and Karlstrom, 2007) were abolished in embryos treated with cyclopamine at 50% epiboly, whereas dimethyl sulfoxide (DMSO) -treated embryos displayed normal expression of these markers.…”
Section: Characterization Of Dbx Gene Expression In Zebrafish Spinal supporting
confidence: 92%
“…In fact, sequence comparison between the three genes indicates dbx2 is the most divergent (Seo et al, 1999). Recent reports in zebrafish have shown that many of the spinal progenitor genes have conserved spatial relationships (Cheesman et al, 2004;Lewis et al, 2005;Guner and Karlstrom, 2007). We have demonstrated that the relationship of Dbx expression to other progenitor genes is evolutionarily conserved in zebrafish, which we find intriguing given the size difference of the zebrafish spinal cord compared with amniotes.…”
Section: Conservation Of Dbx Gene Expression In Zebrafishmentioning
confidence: 55%
See 1 more Smart Citation
“…The transcription factor hb9 is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004). In the hb9-GFP transgenic fish, motor neurons are labeled with strong neuron-specific expression of GFP under the control of the regulatory elements of the zebrafish hb9 gene (Flanagan-Steet et al, 2005;Nakano et al, 2005).…”
Section: Live Embryo Imagingmentioning
confidence: 99%
“…Importantly, in another study we also showed that acetyl L-carnitine counteracts ketamine's negative effects on heart rate and ERK (MAPK) activity in zebrafish embryos (Kanungo et al, 2012). In order to quantitate the effect of ketamine on motor neurons in vivo, hb9:green fluorescent protein (hb9:GFP) transgenic zebrafish embryos were used, in which the promoter of the transcription factor hb9 that is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004), drives GFP expression specifically in motor neurons (Flanagan-Steet et al, 2005;Nakano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%